Peraturan Mahkamah Agung No.3 Tahun 2021: Bukti Mahalnya Keadilan di Indonesia - Purba, M Hadyan Yunhas; Sirait, Ningrum Natasya; Siregar, Mahmul; Dedi Harianto (Universitas Medan Area, 2023)
Legal remedies for objections to the decision of the Business Competition Supervisory Commission (